Resonant inelastic x-ray scattering study of bond order and spin excitations in nickelate thin-film structures - Fürsich, Katrin; Haverkort, Maurits W. (Physical review, 2019)
We used high-resolution resonant inelastic x-ray scattering (RIXS) at the Ni L3 edge to simultaneously investigate high-energy interband transitions characteristic of Ni-O bond ordering and low-energy collective excitations of the Ni spins in the rare-earth nickelates RNiO3 (R=Nd, Pr, La) with pseudocubic perovskite structure. With the support of calculations based on a double-cluster model we quantify bond order (BO) amplitudes for different thin films and heterostructures and discriminate short-range BO fluctuations from long-range static order. Moreover we investigate magnetic order and exchange interactions in spatially confined RNiO3 slabs by probing dispersive magnon excitations. While our study of superlattices (SLs) grown in the (001) direction of the perovskite structure reveals a robust noncollinear spin spiral magnetic order with dispersive magnon excitations that are essentially unperturbed by BO modulations and spatial confinement, we find magnons with flat dispersions and strongly reduced energies in SLs grown in the (111)pc direction that exhibit collinear magnetic order. These results give insight into the interplay of different collective ordering phenomena in a prototypical 3d transition metal oxide and establish RIXS as a powerful tool to quantitatively study several order parameters and the corresponding collective excitations within one experiment.
Gesehen am 13.05.2019